(untitled) (Revista Contexto & Saúde, 2025)
Objective: To assess the factors associated with the quality of life of 282 senior caregivers who care for older family members. Method: A quantitative, cross-sectional study conducted through data collection in 2014, using a protocol consisting of the following instruments: sociodemographic questionnaire, Katz Index, Lawton and Brody Scale, CASP-19, Zarit Burden Inventory, Geriatric Depression Scale, Frailty Assessment (based on a five-component phenotype), Spirituality Scale, and Coping Strategies Inventory. Results: The majority of participants were married women who had been caring for their spouses for an average of 9.6 years. It was observed that older caregivers with lower burden levels were 246% more likely to report better quality of life, and for those without depressive symptoms, this likelihood increased to 527%. Non-frail individuals had a 154% higher chance of perceiving better quality of life, as did those with higher levels of spirituality and stronger coping strategies, who showed 65% and 9% greater likelihood, respectively. Conclusion: The findings highlight that a better quality of life is associated with key factors such as lower frailty and caregiver burden, especially in the absence of depressive symptoms. This underscores the importance of evaluating, identifying, preventing, and implementing when necessary through targeted interventions addressing these factors.